Successful Perioperative Combination of High-Dose FVIII Therapy Followed by Emicizumab in a Patient with Hemophilia A with Inhibitors - Okamoto, Shuichi; Suzuki, Nobuaki; Suzuki, Atsuo; Suzuki, Sachiko; Tamura, Shogo; Suzuki, Mochihito; Takahashi, Nobunori; Kojima, Toshihisa; Kanematsu, Takeshi; Kojima, Tetsuhito; Kiyoi, Hitoshi; Ishiguro, Naoki; Matsushita, Tadashi (TH Open, 2019)
We managed perioperative hemostasis for a 72-year-old man with hemophilia A and low inhibitor titers (3 BU/mL), who underwent osteosynthesis for supracondylar fracture of the left humerus. He was treated perioperatively using the combination of high doses of factor VIII (FVIII) with recombinant human Factor VIII Fc fusion protein (rFVIIIFc), followed by emicizumab. On the day of surgery (day 0), he was administered bolus infusion of 150 IU/kg rFVIIIFc, followed by continuous infusion at a dose of 4 IU/kg/h. Emicizumab, 3 mg/kg, was injected subcutaneously once a week, on days 5, 12, 19, and 26. Inhibitors were detected on day 6 at a titer of 4 BU/mL and FVIII:C decreased to below assay sensitivity limits on day 10. The rate of increase in inhibitor titers was high, with inhibitors increasing to 343.4 BU/mL on day 14. The transition of thrombin production by thrombin generation assay (TGA) showed temporary decrease in thrombin production on day 7, although it was restored by day 10, i.e., five days after commencement of emicizumab therapy. Rotational thromboelastometry displayed consistent results with TGA, showing that clotting time was prolonged and the alpha angle decreased to less than measurable levels on day 6, although they were improved by day 10. There were no bleeding-related events or other adverse events throughout the perioperative period. In conclusion, emicizumab was effective for the management of perioperative hemostasis after development of an anamnestic response in a patient with hemophilia A with inhibitors. Combination therapy with high doses of FVIII followed by emicizumab could be a workable alternative for patients with hemophilia A with inhibitors.
Keywords: factor VIII inhibitors; surgery; hemophilia therapy